Analysis of entrepreneurial readiness of family welfare education study program students concentrating in culinary arts - Hamid, Yuli Heirina; Fadhilah, Fadhilah; Suhairi, Laili; Gagarin, Yuri; Abdullah, Abdullah (Jurnal Pendidikan Vokasi, 2023)
Research on student readiness for entrepreneurship is very important to understand how to enter the business world better. This study aims to describe the entrepreneurial readiness of students of the Family Welfare Education Study Program specializing in Culinary Arts at Syiah Kuala University. This type of research is descriptive quantitative. The study population was 150, with a sample of 100 students. The sampling technique used is proportional random sampling. Data collection was done using a questionnaire that was tested for validity and reliability. Data were analyzed through descriptive analysis using the assessment categorization method based on the average score and percentage assessment. The results concluded that the entrepreneurial readiness of students is in the moderate category. This study shows that the personality, motivation, skills, and knowledge of students are not sufficient to foster entrepreneurial readiness, especially in the Family Welfare Education Study Program specialization in Culinary Arts, Syiah Kuala University. This research will make a new contribution to the academic literature related to student entrepreneurial readiness, especially in the context of the Family Welfare Education Study Program with a concentration in Catering, by enriching our understanding of the factors that influence student readiness to run a business in the culinary field.